THE EFFECT OF ERP-SAP IMPLEMENTATION (ENTERPRISE RESOURCE PLANNING - SYSTEM APPLICATION AND PRODUCT IN DATA PROCESSING) ON THE QUALITY OF ACCOUNTING INFORMATION WITH PERSONAL COMPETENCY PROCESSING DATA AS MODERATING VARIABLES (Study at PT. Perkebunan Nusanta - Sinambela, Ady Putra (Asosiasi Dosen Akuntansi Indonesia, 2021)
This study was conducted to determine the effect of ERP-SAP Implementation on the Quality of Accounting Information and to determine the effect of ERP-SAP Implementation on the Quality of Accounting Information through personal competency in data processing based on HR in companies by seeing that before the ERP there was a gap that made the company's accounting information system become hampered and inefficient. This research uses quantitative methods which are also often called traditional methods because this method has been used for a long time. This method is a scientific method because it is objective, measurable, rational, and systematic. The sample used is the employees of PT. Perkebunan Nusantara III (Persero) Medan as many as 110 people using SEM (Structural Equation Modeling) methods and data analysis. The results showed that the implementation of ERP-SAP had a positive and significant effect on the quality of accounting information and the influence of personal competence in data processing did not significantly moderate the relationship between ERP-SAP implementation and the quality of accounting information at PT. Perkebunan Nusantara III (Persero) Medan.